Health index analysis on asset management and the influence of electricity and environmental safety aspects on overhead transmission line 150 kV Anyer – Asahimas - Murtado, Muhammad Saidul; Setiabudy, Rudy (Universitas Negeri Padang, 2022)
The availability and reliability of electrical energy has become the backbone of society, so periodic maintenance needs to be carried out to avoid short breakdowns and technical malfunctions as well as to improve electrical and environmental safety. Overhead transmission line is an important part of the transmission network and their health status is an important foundation for ensuring the reliable supply of electricity to the power grid. The health index (HI) is a value that reflects the health status of high-voltage transmission lines obtained by combining the normalization of component ratings on certain parameters and calculation methods. This study shows that the condition of assets, electricity and the environment have an effect on determining the soundness index of the Anyer-Asahimas 150 kV overhead transmission line and can be a guide for its maintenance. The final health index value shows 92.8% meaning that the transmission is not only safe in terms of equipment but also safe in terms of electrical and environmental safety aspects.